Multifaceted Role of PARP-1 in DNA Repair and Inflammation: Pathological and Therapeutic Implications in Cancer and Non-Cancer Diseases - Simonetta Pazzaglia; Claudio Pioli (Cells, 2019)
PARP-1 (poly(ADP-ribose)-polymerase 1), mainly known for its protective role in DNA repair, also regulates inflammatory processes. Notably, defects in DNA repair and chronic inflammation may both predispose to cancer development. On the other hand, inhibition of DNA repair and inflammatory responses can be beneficial in cancer therapy and PARP inhibitors are currently used for their lethal effects on tumor cells. Furthermore, excess of PARP-1 activity has been associated with many tumors and inflammation-related clinical conditions, including asthma, sepsis, arthritis, atherosclerosis, and neurodegenerative diseases, to name a few. Activation and inhibition of PARP represent, therefore, a double-edged sword that can be exploited for therapeutic purposes. In our review, we will discuss recent findings highlighting the composite multifaceted role of PARP-1 in cancer and inflammation-related diseases.